Assessment of serum lactate levels, blood glucose values and blood gas values in sheep, newborn lambs and placenta - Silva, Leticia Peternelli; Lourenço, Maria L.G. [UNESP]; Paula, Renata A. [UNESP]; Verdugo, Mirela R. [UNESP]; Pereira, Keylla H.N.P. [UNESP]; Chiacchio, Simone B. [UNESP] (FapUNIFESP (SciELO), 2018)
Newborn animals, in the fetal-to-neonatal transition, usually face several challenges in their first 24 hours, including issues with acid-base balance, glycemic levels and oxygenation. Difficulties to overcome such issues have caused several deaths among newborns. Therefore, studies have been carried out in order to evaluate them. The main purpose of this study is to evaluate the correlation between the serum lactate level in the mother, in the placenta and in the newborn. Moreover, the study measured the lactate level, blood glucose level and blood gas level in the first 24 hours. Tests were carried out right after birth, and at 4, 8, 12 and 24 hours after. Lactate levels were quite similar to the placental levels (p=0.991) which, in turn, were significantly different from the mother’s (p=0.011). Results showed that, shortly after birth, the production of lactate in the placenta is part of the issue. Along the first 24 hours, the study observed a reduction of the levels of lactate in newborns; the levels were closer to the normal index levels for the species. Regarding the blood gas test results, we observed mild metabolic acidosis at birth; acid-base balance was completely stable at the end of the period.
Keywords: Blood gas; Blood glucose; Ewes; Lactate; Lambs; Newborn; Physiology; Placenta; Serum lactate; Sheep